Program Pembinaan Mental Health Siswa Kelas VIII di SMP Darul Hikam Bandung - Intan Indah Permatasari; Sobar Al Ghazal; Nurul Afrianti (Jurnal Riset Pendidikan Agama Islam, 2025)
Abstract. Mental Health plays an important role in adolescent development. The problem in this research is formulated as follows: (1) What is the Mental Health profile of students? (2) What are the forms of Mental Health coaching programs? (3) How are organization of Mental Health coaching programs? (4) How are Involvement of Islamic Religious Education teachers in Mental Health coaching programs? (5) What are the factors that hinder the implementation of Mental Health coaching programs?. Researcher using qualitative approach and a case study research design. Data collection techniques used in this study were observation, interviews, and documentation. Data analysis technique used in this research is the Miles and Heberman model analysis, which consists of data reduction, data presentation, and conclusion drawing. The results of this study are: The condition of Mental Health problems experienced by class VIII students at SMP Darul Hikam Bandung include stress and overthinking. Coaching program Mental Health is conducted through the PIKR.DH community and structured halaqah sessions in the planning, implementation, and evaluation stages. Islamic Religious Education teachers actively participate in the halaqah sessions every Friday. The factors hindering progress stem from the students' emotions and time constraints in the implementation of PIKR.DH. Abstrak. Kesehatan Mental berperan penting dalam perkembangan remaja. Permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Bagaimana gambaran Mental Health Siswa? (2) Bagaimana bentuk program pembinaan Mental Health Siswa? (3) Bagaimana pengorganisasian program pembinaan Mental Health Siswa? (4) Bagaimana keterlibatan guru Pendidikan Agama Islam dalam program pembinaan Mental Health Siswa? (5) Apa saja faktor-faktot yang menghambat dalam pelaksanaan program pembinaan Mental Health Siswa?. Peneliti menggunakan pendekatan kualitatif dan jenis penelitiannya studi kasus. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah observasi, wawancara, dan dokumentasi. Adapun teknik analisis data yang digunakan dalam penelitian ini adalah teknik analisis data model Miles dan Heberman terdiri dari reduksi data, penyajian data, dan penarikan kesimpulan. Hasil dari penelitian ini adalah: Kondisi masalah Kesehatan Mental yang dialami oleh siswa kelas VIII di SMP Darul Hikam Bandung mengalami stres dan overthinking. Program pembinaan Mental Health dilakukan melalui komunitas PIKR.DH dan halaqah yang terstruktur dalam tahapan perencanaan, pelaksanaan, dan evaluasi. Guru PAI berperan aktif dalam kegiatan halaqah setiap Jumat. Faktor penghambat berasal dari emosi siswa dan kendala waktu dalam pelaksanaan PIKR.DH.